2013
DOI: 10.1105/tpc.113.113399
|View full text |Cite
|
Sign up to set email alerts
|

The Deubiquitinating Enzyme AMSH1 and the ESCRT-III Subunit VPS2.1 Are Required for Autophagic Degradation inArabidopsis     

Abstract: In eukaryotes, posttranslational modification by ubiquitin regulates the activity and stability of many proteins and thus influences a variety of developmental processes as well as environmental responses. Ubiquitination also plays a critical role in intracellular trafficking by serving as a signal for endocytosis. We have previously shown that the Arabidopsis thaliana ASSOCIATED MOLECULE WITH THE SH3 DOMAIN OF STAM3 (AMSH3) is a deubiquitinating enzyme (DUB) that interacts with ENDOSOMAL COMPLEX REQUIRED FOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
93
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 81 publications
1
93
0
3
Order By: Relevance
“…In mammalian cells, it has been found that autophagosomes can either fuse directly with lysosomes or fuse first with endosomes to form intermediate compartments called amphisomes, which subsequently fuse with the lysosome (6). In plants, the exact role of MVBs in autophagy remains elusive, even though a recent report has demonstrated a requirement for ESCRT-III in autophagic degradation (13). Because FREE1 is essential for the proper formation of MVBs, it is likely that loss of FREE1 might inhibit either the fusion of autophagosomes with MVBs or the fusion of amphisomes with vacuoles.…”
Section: Free1 Depletion Increases the Association Between Autophagosmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian cells, it has been found that autophagosomes can either fuse directly with lysosomes or fuse first with endosomes to form intermediate compartments called amphisomes, which subsequently fuse with the lysosome (6). In plants, the exact role of MVBs in autophagy remains elusive, even though a recent report has demonstrated a requirement for ESCRT-III in autophagic degradation (13). Because FREE1 is essential for the proper formation of MVBs, it is likely that loss of FREE1 might inhibit either the fusion of autophagosomes with MVBs or the fusion of amphisomes with vacuoles.…”
Section: Free1 Depletion Increases the Association Between Autophagosmentioning
confidence: 99%
“…New light has been thrown onto this situation through the discovery that ESCRT is also involved in autophagy. More and more studies on nematodes, flies, mammals, and even on plants provide evidence to support the conclusion that the inactivation of ESCRT machinery causes an accumulation of autophagosomes (9)(10)(11)(12)(13). Different models, such as the induction of autophagy or the disruption of autophagosome-endosome/lysosome fusion, have been proposed to explain the observation that autophagosomes accumulate in ESCRT-depleted cells (14,15).…”
mentioning
confidence: 95%
“…One of these complexes, ESCRT-III, associates directly with endosomal membranes and is thought to mediate changes in the membrane architecture that ultimately lead to intraluminal vesicle scission (Schuh and Audhya, 2014). Studies with Drosophila melanogaster, Caenorhabditis elegans, plants, and mammalian cells showing that ESCRT mutants hyperaccumulate autophagosomes (Roudier et al, 2005;Filimonenko et al, 2007;Lee et al, 2007;Rusten et al, 2007;Rusten and Stenmark, 2009;Djeddi et al, 2012;Katsiarimpa et al, 2013) implied that the ESCRT machinery plays a role in autophagy. Given that the scission of nascent intraluminal vesicles at endosomes and the closure of phagophores into sealed autophagosomes are topologically similar, ESCRT proteins could participate directly in phagophore closure.…”
Section: Introductionmentioning
confidence: 99%
“…The induction and conjugation machineries leading to ATG8 lipidation have been characterized 3 [35][36][37][38] , the different steps of the autophagic pathway are not resolved. Moreover, little information is presently available on the morphology of early autophagosomal structures 34 , and the subcellular distribution of the ATG5 complex or the site of autophagosome formation are currently unknown.…”
mentioning
confidence: 99%